Correlation Of Self-Efficiency To Stress And Anxiety Level In Students Who Are Completing The Final Program Of Doctor Education University Of Lampung - Martogi Simalango, Eka Yuliana; Oktafany, Oktafany; Djausal, Anisa Nuraisa; Berawi, Khairun Nisa (Medical Profession Journal of Lampung, 2022)
Thesis is one of the requirements that must be completed by final year students. Writing a thesis requires students to think harder and can cause stress and anxiety. In overcoming this, students need a belief or self-efficacy. This study aims to determine the correlation of self-efficacy to stress and anxiety levels in students who are completing the final project of the Medical Education Study Program, University of Lampung. The design of this study used an observational analytic method with a cross sectional approach. Respondents consisted of 180 students using a total sampling technique. This study uses primary data in the form of a questionnaire. The analysis used is Kruskall-Wallis. There were 109 students (60.6%) experiencing moderate stress and 56 students (31.1%) experiencing mild anxiety. The results showed that there was a significant correlation between self-efficacy and stress levels (p-value 0.006) and there was a correlation between self-efficacy and anxiety levels (p-value 0.001).